The Impact of a Game-Integrated Project-Based Learning Microbiology E-Module on Microbiology Learning Outcomes - Fitriani, Vivi; Bin Borhan, Mohamad Termizi; Binti Tawang, Alena (Biosfer: Jurnal Tadris Biologi, 2026)
The complexity of microbiological concepts requires innovative instructional approaches that can enhance students’ conceptual understanding and engagement. This study aimed to examine the effect of the Microbes electronic module, which is based on Project-Based Learning and integrated with educational games, on students’ learning outcomes in a Microbiology course. The study employed a quantitative approach using a quasi-experimental pretest–posttest nonequivalent control-group design. A total of 93 Biology Education students from two universities in Indonesia participated in the study, comprising 48 students in the experimental group and 45 students in the control group. The intervention was conducted over five instructional sessions covering viruses, bacteria, and fungi. Students in the experimental group learned using the Microbes electronic module, which integrated multimedia learning resources, project activities, and gamification elements, whereas the control group received conventional instruction. Data were collected using a validated achievement test consisting of 57 multiple-choice items and analyzed using descriptive statistics, Levene’s test, an independent-samples t test, and Cohen’s d effect-size analysis. The results showed that students in the experimental group achieved significantly higher learning outcomes than those in the control group, t(91) = 3.59, p < .001, with a mean difference of 8.10 points. The effect-size analysis yielded a Cohen’s d of 0.74, indicating a moderate-to-large effect. These findings suggest that integrating PjBL, multimedia, and educational games into a digital module can improve students’ understanding of microbiological concepts. Dampak Modul Elektronik Mikrobiologi Berbasis Project-Based Learning yang Terintegrasi Permainan Edukatif terhadap Hasil Belajar Mikrobiologi ABSTRAK: Kompleksitas konsep dalam mikrobiologi menuntut adanya pendekatan pembelajaran inovatif yang mampu meningkatkan pemahaman konseptual dan keterlibatan mahasiswa. Penelitian ini bertujuan untuk menganalisis pengaruh modul elektronik Microbes berbasis Project-Based Learning yang terintegrasi dengan permainan edukatif terhadap hasil belajar mahasiswa pada mata kuliah Mikrobiologi. Penelitian ini menggunakan pendekatan kuantitatif dengan desain kuasi-eksperimen pretest–posttest nonequivalent control group. Penelitian melibatkan 93 mahasiswa Pendidikan Biologi dari dua universitas di Indonesia, yang terdiri atas 48 mahasiswa pada kelompok eksperimen dan 45 mahasiswa pada kelompok kontrol. Intervensi dilaksanakan selama lima pertemuan pembelajaran yang mencakup materi virus, bakteri, dan jamur. Mahasiswa pada kelompok eksperimen belajar menggunakan modul elektronik Microbes yang mengintegrasikan sumber belajar multimedia, aktivitas proyek, dan unsur gamifikasi, sedangkan kelompok kontrol memperoleh pembelajaran konvensional. Data dikumpulkan menggunakan tes hasil belajar tervalidasi yang terdiri atas 57 soal pilihan ganda dan dianalisis menggunakan statistik deskriptif, uji Levene, uji t sampel independen, dan analisis ukuran efek Cohen’s d. Hasil penelitian menunjukkan bahwa mahasiswa pada kelompok eksperimen memperoleh hasil belajar yang secara signifikan lebih tinggi dibandingkan kelompok kontrol, t(91) = 3,59, p < 0,001, dengan selisih rata-rata sebesar 8,10 poin. Analisis ukuran efek menghasilkan Cohen’s d sebesar 0,74, yang menunjukkan efek sedang hingga besar. Temuan ini menunjukkan bahwa integrasi PjBL, multimedia, dan permainan edukatif dalam modul digital dapat meningkatkan pemahaman mahasiswa terhadap konsep mikrobiologi.